(untitled) (Papeles, 2019)
How do economists value anything in order to understand that certain amount of goods worth the same as another amount of goods, or money? How do they value a group of heterogeneous things in order to make simple arithmetic operations? The answers to these and some similar questions lead us to the theory of value, and this paper aims to present, in a didactical way, a single conceptual aspect: the unity of the value measurement. Any economic scholar knows that value has a huge complexity because it is related to some other essential theorical aspects, such as the theory of capital, the theory of production, and the theory of distribution. This document does not deal with such topics, although it has to mention them superficially. Its purpose is to briefly present why a unity of the value measurement is needed, and the difficulties faced by the economic theories in their searches, always taking in mind a reader with few bases in economics (specialists should turn to other books that deal with that topic). In order to achieve its purpose, the text was written in a progressive way: from classical to contemporary economical thinking, from simple cases to complex ones. Therefore, the first part of the paper deals with the origin of the necessity of value measurements. Then it shows why the theory of value is important (such as the importance of its measurement), what leads us to explain the requirements that a value measurement must fulfil, and which sorts of solutions have been suggested along the time; finally, it closes with a general conclusion